Production and crystallization of sugar from tapioca - Nor Farhana, binti Hamid (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study explains the best mixing ratio of tapioca starch to distilled water during hydrolysis and the optimum oven drying temperature during crystallization of the sugar syrup. Tapioca (Manihot esculenta) is one of the starchy materials that can be hydrolyzed to produce glucose. Production of sugar was performed from hydrolysis of tapioca flour (TF) and fresh tapioca (FT). Exactly, 500g of either TF or FT were mixed with 500ml, IOOOml, and l500ml at dilution ratio 1:1, I :2, and I :3, respectively. The starch slurries of TF and FTwere enzymatically hydrolyzed for 6 hours (2 hours for liquefaction and 4 hours for sachharification). The hydrolysate was purified by filtration using powdered activated charcoal (PAC) and the purified sugar (TF and FT) were dried at 60°C, 70°C and 80°C. It was observed that the highest glucose recovery obtained in dilution 1:1 with TF (86% at 338g1L) and FT (43% at 156g1L).This result followed by dilution 1:2 which 68% (263g1L) produced from TF and 41 % (\ 39g1L)produced from FT . The lowest glucose recovery was exhibited in dilution 1:3 which TF, (55% at 207g1L) and FT, (32% at 96g1L). For drying of sugar, at 60°C, 70°C and 80°C, TFS achieved to dry completely after 12, 10 and 18 days so as recovered 97%, 97% and 93% of glucose, respectively. At the same temperature, FTS achieved to dry completely after 12, 10, and 18 days, so as recovered 83%, 83%, and 79% glucose, respectively. Therefore, the result confirmed that dilution 1:1 (500g/500ml) was selected as the best dilution ratio for efficient enzymatic hydrolysis. Whereas, 70°C was the suitable drying temperature for TFS and FTS to obtain optimum solidified sugar.